Analysis of Kudoa thyrsites (Myxozoa: Myxosporea) spore antigens using monoclonal antibodies. - Chase, JC; Dawson-Coates, JA; Haddow, JD; Stewart, MH; Haines, LR; Whitaker, DJ; Ken, ML; Olafson, RW; Pearson, TW (2001)
A method employing Percoll gradient centrifugation was developed to purify Kudoa thyrsites spores from somatic muscle tissue of Atlantic salmon Salmo salar. Highly purified spores were then used to immunize inbred BALB/c mice for derivation of hybridomas secreting Kudoa-specific monoclonal antibodies (mAbs). Analysis of mAbs by immunofluorescence microscopy and flow cytometry showed that several were specific for antigens on the surface of K. thyrsites spores whereas other mAbs reacted with polar capsules or with polar filaments of spores of K. thyrsites, K. paniformis and K. crumena. Immunoblots on spore lysates using the surface-binding mAbs showed a broad band of 46 to > 220 kDa, whereas mAbs specific for antigens of polar capsules and polar filaments detected sharper bands of various molecular masses, depending on the Kudoa species. The dominant epitope of the K. thyrsites spore surface antigen was shown to be carbohydrate as determined by its sensitivity to treatment with anhydrous trifluoromethane sulfonic acid and by its resistance to treatment with Proteinase K. Immunofluorescence microscopy using the K. thyrsites-specific mAbs on isolated, intact, permeabilized plasmodia and on thin sections of somatic muscle tissue containing plasmodia revealed intense labeling of spores both within the spore-producing plasmodia and in the flesh of infected Atlantic salmon. As few as 100 spores were detected by immunoblotting, indicating that these mAbs have potential for use in developing a field-based diagnostic test.